Consensus tracking for multi-motor system via observer based variable structure approach - Zhang, Changfan; Wu, Han; He, Jing; Xu, Chengjie (Journal of the Franklin Institute, 2015)
This study investigates a leader–follower consensus tracking algorithm for synchronous coordination control of shaftless-driven printing press (SDPP), which can be regarded as a multi-motor system (MMS). With consideration of tracking and synchronization performance optimization, the control algorithm is proposed under two premises. The first is that the leader has directed paths to all followers, and this path is easy to implement in a practical SDPP system. The second is that each follower coordinates its motion with other followers in the presence of only local interactions, which guarantees synchronization precision and avoids intensive on-line computational work. By employing an observer-based variable structure algorithm, we improve the robustness and estimate the uncertainties for chattering elimination. Theoretical analysis indicates that all followers globally, exponentially, and asymptotically converge to a time-varying leader under the given conditions. Simulation results illustrate the efficient performance of the suggested algorithm in terms of synchronization control accuracy, disturbance immunity, and convergence.